2015
DOI: 10.1039/c5cy00251f
|View full text |Cite
|
Sign up to set email alerts
|

(Pd–CuCl2)/γ-Al2O3: a high-performance catalyst for carbonylation of methyl nitrite to dimethyl carbonate

Abstract: (Pd–CuCl2)/γ-Al2O3 catalyst with excellent activity and selectivity was successfully developed for vapor-phase carbonylation of methyl nitrite to dimethyl carbonate (DMC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Subsequently, palladium methoxy carbonyl intermediate can be generated via the insertion of the adsorbed CO molecule. 17,23,29,31 It was suggested that DMC is produced by the reaction between palladium methoxy carbonyl intermediates and MN from the atmosphere, while DMO is obtained by the coupling between two palladium methoxy carbonyl intermediates. 1,17,23,31 However, the outstanding question remains of why the Pd(II)based catalysts favor the creation of DMC, while Pd(0)-based catalysts favor DMO.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequently, palladium methoxy carbonyl intermediate can be generated via the insertion of the adsorbed CO molecule. 17,23,29,31 It was suggested that DMC is produced by the reaction between palladium methoxy carbonyl intermediates and MN from the atmosphere, while DMO is obtained by the coupling between two palladium methoxy carbonyl intermediates. 1,17,23,31 However, the outstanding question remains of why the Pd(II)based catalysts favor the creation of DMC, while Pd(0)-based catalysts favor DMO.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The peaks at 1720 and 1191 cm −1 are ascribed to the CO and C−O stretching vibrations of adsorbed *COOCH 3 intermediates. 29 Moreover, the peak at 1450 cm −1 is assigned to the C−H deformation of adsorbed *COOCH 3 intermediates on catalyst surface. Strong new peaks appear at 1770 and 1303 cm −1 with the passing of time, which are ascribed to the CO and C−O stretching vibrations of gaseous DMC product, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The final NH 3 desorption peak above 330 °C was indexed to strong acid sites, which is associated with the NH 3 adsorbed on Brønsted acid sites. 78,79 In the cases of UiO-66(Zr) and 3.2%-PS/UiO-66(Zr), a broad desorption signal was observed between 150 and 330 °C, suggesting the presence of rich medium acid sites. The amount of NH 3 desorbed from these acid sites was calculated by integrating the area under the TPD curves.…”
Section: Resultsmentioning
confidence: 99%